2019
DOI: 10.1111/avj.12859
|View full text |Cite
|
Sign up to set email alerts
|

Bovine digital dermatitis in Victoria, Australia

Abstract: Aims The objectives of this study were to estimate the prevalence of digital dermatitis (DD) in Victoria, Australia, and to investigate which organisms are consistent with typical DD lesions. The prevalence and causative pathogens of DD are not clear yet in Australia and this paper is one of the first to explore these questions in this country.Methods Examination and sampling of limbs was undertaken at three knackeries in Victoria, Australia. Limbs were classified as normal (N), active DD-lesion (A), dried or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
(86 reference statements)
2
10
1
Order By: Relevance
“…Treponema has been the most common genus implied as an etiologic agent of DD. Consistent with this study, virtually every other metagenomic study of DD observes a higher relative abundance of Treponema in most DD lesions compared to normal skin (Krull et al, 2014;Zinicola et al, 2015b;Marcatili et al, 2016;Nielsen et al, 2016;Hesseling et al, 2019). Conversely, it is not uncommon to see some healthy skin samples to also have high proportions of at least one species of Treponema (Beninger et al, 2018;Caddey et al, submitted for publication).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Treponema has been the most common genus implied as an etiologic agent of DD. Consistent with this study, virtually every other metagenomic study of DD observes a higher relative abundance of Treponema in most DD lesions compared to normal skin (Krull et al, 2014;Zinicola et al, 2015b;Marcatili et al, 2016;Nielsen et al, 2016;Hesseling et al, 2019). Conversely, it is not uncommon to see some healthy skin samples to also have high proportions of at least one species of Treponema (Beninger et al, 2018;Caddey et al, submitted for publication).…”
Section: Discussionsupporting
confidence: 83%
“…There is previous literature showing Fusobacterium as differentiating DD lesions from healthy skin (Sullivan et al, 2015;Nielsen et al, 2016;Moreira et al, 2018), but is suggested to have a larger role in chronic lesions due to it being more prevalent in those lesions (Hesseling et al, 2019). We did not identify Fusobacterium in any of the samples from V1V3 amplification.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Many reports have attempted to elucidate the association of the microbiome of BDD towards disease development [ 11 , 13 , 14 , 15 ]. Surprisingly, for more than 20 years since it emerged as a major problem in the cattle industry in certain countries, studies on BDD have just recently started in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…was established as the dominant pathogen in BDD lesions in Korea [ 16 ], but an emphasis on the plethora of bacteria that was observed is still lacking. Although the majority of studies considered that the main pathogen of BDD is Treponema spp., its polybacterial nature must also be considered in order to understand its pathogenesis [ 15 ]. Therefore, this study analyzed the diversity and phylogenetic relationship of the microbiome of BDD lesions and normal skin from the interdigital space of the cattle using 16S rRNA amplicon sequencing.…”
Section: Introductionmentioning
confidence: 99%